Stakeholders Responsibilities in Functional Teacher Education for Sustainable National Development - Oguntoye, Juliet Ayibakarinate (International Journal of Educational Management, 2025)
There is no nation that can develop beyond her educational standard. Thus, education is seen as a catalyst for social, economic and political standard of life of a nation. Functional education is the education in which the ability to perform productive tasks is more emphasized than the education that aims at producing ideological conformity. It is a kind of education that emphasizes practice more than theory. Teacher education as an education for nation builders has great influence in achieving sustainable development goals because it deals with awakening and nurturing of human potentials. Teacher education is the fulcrum of human development for sustainable development. This paper therefore examines the concept of teacher education, functional teacher education, sustainable development and responsibility of every education stakeholder in ensuring functional teacher education for sustainable development. It was oncluded that if Nigeria as a nation would realize sustainable development dream through education, teacher education as an education for nation builders has to be functional and her functionality is the responsibility of every stakeholder such as government, school administrators, teachers, parents and students.